Stationary shapes of axisymmetric vesicles beyond lowest-energy configurations - Reboucas, Rodrigo B; Miksis, Michael J; Vlahovska, Petia M; Faiz, Hammad A (ArXiv.org, 2023)
We conduct a systematic exploration of the energy landscape of vesicle morphologies within the framework of the Helfrich model. Vesicle shapes are determined by minimizing the elastic energy subject to constraints of constant area and volume. The results show that pressurized vesicles can adopt higher-energy spindle-like configurations that require the action of point forces at the poles. If the internal pressure is lower than the external one, multilobed shapes are predicted. We utilize our results to rationalize the experimentally observed spindle shapes of giant vesicles in a uniform AC field.